Acral Fibrochondromyxoid Tumor Presenting as Enlarging Nodule Involving the Distal Fingertip and Hyponychium: A Case Report - Rhiannon C. Miller; Cynthia M. Magro; Laura E Melnick; Shari R. Lipner (Karger Publishers, 2023)
An acral fibrochondromyxoid tumor is a newly described type of benign soft tissue neoplasm that presents as a single nodular lesion on a finger or toe. There has only been one previous report on this tumor, a case series that described the initial pathologic and clinical findings; however, details on clinical history, physical examination, and outcome are unknown. In this report, we describe a case of a 39-year-old male who presented with a painful enlarging mass involving the distal right 3rd finger and hyponychium. Punch biopsy was performed and the lesion was identified as an acral fibrochondromyxoid tumor on microscopic examination. X-ray showed no bony involvement. The tumor was successfully excised with complete resolution of pain symptoms. We discuss the clinical features and immunohistochemistry findings of our case in the context of the current limited knowledge about this very rare tumor.